Knowledge And Practice Of Nursing Documentation: A Cross-Sectional Study In Secondary Care Of King Khalid Hospital, Najran Area, Kingdom Of Saudi Arabia - Alyami, Awad Hussein Mahdi; Alhareth, Mohammad Hamadi Hamad Al; alhareth, Mubarak Saeed Al; ALALHARETH, HUSSAIN MESFER BIN DHAFER; alhareth, Hadi Mesfer dafer al; Alhareth, Ali Mesfer Dafer Al; Alyami, Theyab Hadi; Mahri, Faris Mana AIi AL (Migration Letters, 2023)
Nursing documentation is extremely crucial for nurses. A healthcare service delivery system was examined using a conventional data collection method. As a result, nurses and other healthcare workers must ensure that their job is precisely and efficiently documented. This helps them defend themselves legally, provides better patient care, and increases communication among healthcare practitioners. However, there is insufficient study available on this subject. This study aimed to determine what nurses in emergency departments of government hospitals in the Najran area, Kingdom of Saudi Arabia, know and believe about nursing documentation.. A study was conducted in the emergency departments of government hospitals in the Najran area of Saudi Arabia. We utilized a simple way to collect numerical data. We collected data using a questionnaire and a review of records. Data collectors and supervisors had two days of training. We generated certain numbers to represent the data and then presented the results in the form of graphics, charts, and text. In this study, 400 individuals were enrolled, with a mean age of 31.77 years; 41.5% were men, 58.5% were females; the majority of participants were married (65.8%), 15.8% were single, 10.8% were divorced, and 7.7% were widows. In terms of education, 47.5% had a BSC, 26.5% had an MSC, and 26% had a diploma. 83% of participants had good knowledge of nursing documentation, while 17% had poor knowledge, with a mean total score of 7.5 and an average score of 0.83. We identified strong correlations between overall knowledge and personal variables, including age, gender, marital status, educational level, and work experience (p value <0.001). We identified significant relationships between overall attitude and personal data, including age, gender, marital status, educational level, and work experience (p-value < 0.001). This study found that nurses write down and record information more effectively than in previous studies. The researchers advise that nurses should be more aware of, have a positive attitude toward, be conversant with, and devote adequate time to nursing documentation practice. Furthermore, it is essential to monitor and compare nursing paperwork in order to perform future research.